Klasifikasi Kesiapan Anak Taman Kanak-Kanak Masuk Sekolah Dasar Menggunakan Metode Naive Bayes - Yuli Praptomo Pamungkas Hari Sungkowo; Deni Ambarwati (Universitas Muhammadiyah Purworejo, 2023)
In accordance with government regulations that prospective new students in grade 1 (one) elementary school must meet the age requirements of 7 (seven) years; or at least 6 (six) years on July 1 of the current year. In addition to the age factor, there are other aspects that affect the readiness of kindergarten children to enter elementary school, namely cognitive, gross motor, fine motor, language, and social emotional aspects. However, many students enter elementary school although there are still some aspects that cannot be fulfilled. Therefore, a classification is needed to find out whether these students have readiness to enter the elementary school level or not. The classification of children's readiness to enter elementary school in this study uses the nave Bayes method, with attributes used include age, ability to read, write, count, and independence. The results of this study are to determine the readiness of students to enter elementary school so that later students and teachers will not be overwhelmed in participating in teaching and learning activities. Based on the test results, obtained an accuracy value of 94.23%. From the test results, it can be concluded that the Naïve Bayes method can be used to classify students' readiness to enter elementary school.